Bilateral Complex Regional Pain Syndrome Associated with Lumbar Disc Herniation - Necmettin YILDIZ,; Gonca ÖDEMİŞ GÜNGEN,; Olga YAYLALI,; Füsun ARDIÇ, (Archives of Rheumatology, 2011)
Complex regional pain syndrome (CRPS) is a syndrome characterized by a combination of pain, trophic changes, and vasomotor disturbances. Although the case reports in the literature describing the CRPS secondary to lumbar disc herniation (LDH) are abundant, in these case reports CRPS is diagnosed in only one extremity. Based on the most recent information available, this is the first case of CRPS associated with LDH that developed in bilateral lower extremities and could be successfully treated conservatively. A 49-year-old male patient was admitted to the clinic with complaints of pain and swelling of both feet and ankles, particularly on the left side. The patient had a history of an episode of low back pain radiating down the left leg that had developed two months previously after bending and lifting. Lumbar magnetic resonance imaging showed posterocentrally- and bilateral paramedially-located L5-S1 disc protrusion. One month after the onset of low back pain, painful stiffness and swelling developed in the joints of both ankles and feet, accompanied by edema, hyperhydrosis and allodynia in the dorsum of the left foot. He did not have any history of trauma. The medical history and laboratory investigations were normal. A diagnosis of CRPS in bilateral lower extremities was confirmed by direct foot-ankle radiographs and three-phase bone scintigraphy. A comprehensive conservative treatment program consisting of drug treatment (nonsteroidal anti-inflamatory drugs, gabapentin and calcitonin), physical therapy, and rehabilitation methods consisting of active-passive range of motion exercises to both ankles with gentle stretching, desensitization activities, gait training, application of a hot pack, ultrasound and transcutaneous electrical nerve stimulation to the lumbar region were applied. The patient's symptoms were relieved by these conservative treatments in six weeks. No recurrence occurred after a follow-up of 12 months. CRPS should be considered as a cause of persistently painful and swollen bilateral lower extremities in a patient with LDH. Early, accurate diagnosis should permit initiation of appropriate treatment and increase the success of the treatment.